Gynecological Cancer as a Second Malignancy in Patients With Breast Cancer. Issue 6 (July 2017) - Yadav, Budhi Singh; Sharma, Suresh C.; Patel, Firuza D.; Rai, Bhavana; Ghoshal, Sushmita
Abstract : Purpose: The aim of this study was to determine the incidence and risk factors for gynecological cancer as second malignancy (SM) after treatment of breast cancer (BC). Methods and Materials: Between January 1985 and December 2007, a total of 2756 patients with BC were analyzed for gynecological cancers as an SM. Analysis was carried out for patient-, disease-, and treatment-related characteristics. The Cox proportional hazards regression model was used to estimate the relative risk of gynecologic malignancies. Results: The median age at BC diagnosis was 49 years and median follow-up of 14 years. In total, 25 cases of gynecological cancer were noted with an incidence of 0.9%. We observed 9 ovarian and endometrium (0.3%) as well as 7 uterine cervix (0.25%) cancers. Family history of BC was the most significant risk factor for SM (relative risk, 7.4; 95% confidence interval, 3.03–18.28; P <0.001). Women with a family history of BC had a higher incidence of endometrial (12%) and ovarian (16%) cancer compared with those who have no family history (0.1%, P = 0.003). Statistically significant higher incidence of endometrial cancer was seen in patients undergoing hormonal therapy (0.4%) as compared with those who are not undergoing hormonal therapy (0.1%, P = 0.001). Most of the endometrial (88.9%) and cervical (71%) cancers were detected at an early stage but ovarian cancers (66.6%) in advanced stage. Chemotherapy and radiotherapy did not increase the risk of gynecological SM. Conclusions: Women with BC are at risk of developing a second primary gynecological malignancy particularly of endometrium and ovary. Family history of BC was a high risk factor for gynecologic SM. These patients should be followed up for its early detection.